Quality of the relationships with the media and their impact on the journalistic contents - Cortez Gaona, Karen (2015)
This research addresses one of the functions of public relations exercise: management with the media. Supported by the ethical and collaborative relationship with the media the correlation between the quality of relations with the media from an organization with the publication of newspaper media on this, according to the levels of trust, satisfaction and commitment demonstrated linked in his reason as a journalistic source, journalistic relevance of the content and / or events of the organization; and the reality constructed by the media print news media investigated: El Comercio, Gestión, Perú 21, La República, Correo, La Primera y Expreso. This descriptive-correlational, not experimental, qualitative and quantitative research shows that the quality of relationships does influence news content. Based on the results found, it is stated that there is a correlation level of 71.8%, which is a clear indicator of high-level existing between the variables.